Epidemiology of sepsis in Siriraj Hospital 2007. - Nasikarn Angkasekwinai (2018)
BACKGROUND: Sepsis remains a major health burden, and there is limited epidemiological report of sepsis in Thailand. OBJECTIVE: To determine the epidemiology, treatments, clinical courses and outcomes of sepsis patients. MATERIAL AND METHOD: All sepsis patients in medical wards at Siriraj Hospital were recruited from February 1 to July 31, 2007. The information from patients' medical records were retrieved and analyzed. RESULTS: From 3,451 patients, 201 (5.8%) were diagnosed as sepsis, and 38.8% of these developed septic shock. Among sepsis patients, 62.2% were community acquired, 40.8% had bacteremia, and gram negative bacteria were the common pathogen (51.7%). Appropriate antibiotics were given within 6 hours in 39%. Goal-directed therapy was achieved in only 11.5%. The mortality among sepsis and septic shock patients was 34.3% and 52.6%, respectively (p = 0.008). Risk factors for hospital mortality included higher maximum SOFA score, hospital-acquired infection, central nervous system dysfunction and receiving antibiotics after 6 hours of onset of sepsis. CONCLUSION: Sepsis is still common and has contributed to high mortality. Goal directed therapy and appropriate antibiotics given within 6 hours might improve the outcome.